Temperature Regulation (Iowa NIC) In: Nursing interventions classification (NIC): Iowa intervention project (2nd ed) - McCloskey JC; Bulechek GM (Temperature Regulation (Iowa NIC) In: Nursing Interventions Classification (NiC): Iowa Intervention Project (2nd Ed), 1996)
SCOPE NOTE: Attaining and/or maintaining body temperature within a normal range. Use only as a specific Iowa Nursing Interventions Classification. Copyright (c) 1996, Mosby-Year Book, Inc. CINAHL EDITORIAL SEARCH SUGGESTION: The term TEMPERATURE REGULATION (IOWA NIC) is used for indexing when articles specifically concern the term or research about the term. For citations that concern the general topic or topics related to the term, consider searching the subject heading: BODY TEMPERATURE REGULATION.